Dosis de pollinaza y ceniza en el carbono acumulado y fotosíntesis del Zea mays L(maíz morado) en Iquitos - Tello Lopez, Patty (2025)
The rehearsal settled in the Garden Agrostológico, the objective was to determine the level of the payments (pollinaza but ash) in the corn lived with respect to the accumulation of carbon and photosynthesis, evaluated to the 42 days after carrying out an uniformización cut to the grass in study, to achieve the objective the DBCA it was used with four treatments and three reproductions, the, universe was conformed by cultivation of lived corn installed 0.50 x 0.50, they took the samples at random which were conformed by four plants by each treatment, being ended up concluding that: the pollinaza levels but ash applied to the cultivation if they have significant effects; with respect to the green matter with averages of (3.10, 3.00, 2.80 and 2.00 kg/m2), dry matter (0.644, 0.624, 0.582 and 0.416 kg/m2) accumulated carbon (0.25, 0.24, 0.22 and 0.16 g/m2) and photosynthesis (0.055, 0.052, 0.048 and 0.035% /m2), therefore the hypothesis is accepted outlined the pollinaza levels since but ash if they influence in the agronomic characteristics, accumulated carbon and photosynthesis.